(3TQM GdebGeGJ GdMQjQjs - (3YHO Gddg Hf GdMSjf Hf YHO Gddg GdYcHQj GdHZOGOj, CHh GdHbGA, eMH GdOjf,J (B616 (3g` s; (3GdMQjQj,J (B516 (3g` s ((3CHi RcQjG ceGd GdOjf jMji Hf eMeO Hf Oda Hf CHj WGdH Hf Oda GdebQF s)
(3ChdgG (B:s
(3CeG HYO aEfi deG QCjJ GdebGeGJ GdMQjQjI eTMhfI HGdCdaGX GddZhjI hgj CMO GdcJH GdJi Yfi HgG YdeGA GdYQHjI s
(3BNQgG (B:s
(3hNW GdTjH QCSg NGdWjg GdShGO hGdHPF GdeJcde HGdaMT jbGd QLd HPF hGeQCI HPjFI hGdQbhH (B: (3GdeQCI GdJi dG jYjT dgG hdO Je TQM GdebGeGJ s
(3GdfSNI ebGHdI Ydi GdCUd GdebQhA Ydi GdTGQMs
(3HGdeYgO fSNI GNQis
(3GfXQ ai GdLRA GdChd Qbe (B560 (3COHs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdCOHs